Bonjour,
5x + (3 + 2x) = 3 - 2x
⇒ 7x + 3 = 3 -2x
⇒ 7x + 2x = 3 - 3
⇒ 9x = 0
⇒ x = 0
7 - 2(x - 3) = 11
⇒ 7 - 2x + 6 = 11
⇒ 7 + 6 - 11 = 2x
⇒ 2x = 2
⇒ x = 1
3(x - 5) = x - (x + 1)
⇒ 3x - 15 = -1
⇒ 3x = -1 + 15 = 14
⇒ x = 14/3
x + x + 1 = x + x + x + 3
⇒ 2x + 1 = 3x + 3
⇒ 1 - 3 = 3x - 2x
⇒ x = -2
Bonjour;
a)
5x +3+2x = 3-2x
7x+3 = 3-2x
7x+2x = 3-3
9x = 0
x= 0
b)
7-2x +6 = 11
13 -2x =11
13-11 = 2x
2= 2x
x= 2/2
x= 1
c)
3x-15 = x-x -1
3x-15 = -1
3x = -1+15
3x = 14
x= 14/3
d)
2x+1 = 3x+3
1-3 = 3x-2x
x = -2
Copyright © 2025 ELIBRARY.TIPS - All rights reserved.
Lista de comentários
Bonjour,
5x + (3 + 2x) = 3 - 2x
⇒ 7x + 3 = 3 -2x
⇒ 7x + 2x = 3 - 3
⇒ 9x = 0
⇒ x = 0
7 - 2(x - 3) = 11
⇒ 7 - 2x + 6 = 11
⇒ 7 + 6 - 11 = 2x
⇒ 2x = 2
⇒ x = 1
3(x - 5) = x - (x + 1)
⇒ 3x - 15 = -1
⇒ 3x = -1 + 15 = 14
⇒ x = 14/3
x + x + 1 = x + x + x + 3
⇒ 2x + 1 = 3x + 3
⇒ 1 - 3 = 3x - 2x
⇒ x = -2
Bonjour;
a)
5x +3+2x = 3-2x
7x+3 = 3-2x
7x+2x = 3-3
9x = 0
x= 0
b)
7-2x +6 = 11
13 -2x =11
13-11 = 2x
2= 2x
x= 2/2
x= 1
c)
3x-15 = x-x -1
3x-15 = -1
3x = -1+15
3x = 14
x= 14/3
d)
2x+1 = 3x+3
1-3 = 3x-2x
x = -2